2007
DOI: 10.3109/s10165-007-0612-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single nucleotide polymorphisms in the human interleukin-10 gene promoter between rheumatoid arthritis patients and normal subjects in Malaysia

Abstract: In this study, three single nucleotide polymorphisms (SNPs) located within the promoter of the human interleukin (IL)-10 gene [rs1800896 (position: -1087G>A), rs1800871 (position: -824C>T) and rs1800872 (position: -597C>A)] were investigated in 84 rheumatoid arthritis (RA) patients and 95 age- and sex-matched healthy subjects using polymerase chain reaction-restriction fragment length polymorphism method. Production of IL-10 by peripheral blood lymphocytes from the RA patients and healthy subjects cultured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…12 The -1082A/G polymorphism is located at putative regulatory regions in the promoter of the IL-10 gene. 13 A number of studies have examined the potential contributions made by À1082A/ G to SLE susceptibility, but Endings are not consistent. 12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] This inconsistency may be due to the low statistical powers of individual studies, racial and ethnic differences, publication bias, or uncorrected multiple hypothesis testing.…”
Section: Introductionmentioning
confidence: 99%
“…12 The -1082A/G polymorphism is located at putative regulatory regions in the promoter of the IL-10 gene. 13 A number of studies have examined the potential contributions made by À1082A/ G to SLE susceptibility, but Endings are not consistent. 12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] This inconsistency may be due to the low statistical powers of individual studies, racial and ethnic differences, publication bias, or uncorrected multiple hypothesis testing.…”
Section: Introductionmentioning
confidence: 99%
“…IL-10 promoter gene polymorphisms may influence the susceptibility to and outcome of viral infection (Helminen et al, 1999;Shrestha et al, 2007;Zhang et al, 2010;Sun et al, 2013). Low IL-10-producing genotypes have been associated with a greater risk for diseases such as inflammatory bowel disease (Tagore et al, 1999), asthma, systemic lupus erythematosus (Hee et al, 2008), and arthritis (Fife et al, 2006;Hee et al, 2007). In our study, the Malaysian Chinese population showed the lowest frequency of the 1082G allele (2%), which is consistent with a previous report in the Chinese populations of Singapore, China, and Taiwan (Trejaut et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For this we selected reported markers/genes from inflammatory pathway and a few oxidative stress pathway genes involved in inflammation. Inflammatory pathway genes were selected as most of the candidate gene studies [11] , [12] , [13] , [14] and GWAS have implicated a role of these genes in RA [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] . Oxidative stress pathway was selected based on evidence of association of genes like SOD3, PON1 and PON2 with joint diseases/RA [25] , [26] , [27] , [28] and their commonly implicated polymorphisms with inflammatory conditions [29] , [30] , [31] , [32] .…”
Section: Introductionmentioning
confidence: 99%